Branching of Main Trunk of Left Coronary Artery and Importance of Her Diagonal Branch in Cases of Coronary Insuficiency - Almira Lujinović; Fehim Ovčina; Alma Voljevica; Aida Hasanović (Biomolecules & Biomedicine, 2005)
Proficiency in the anatomy of coronary arteries and their variations is significant for proper interpretation of the coronary angiographies, assessment of the complexity and result of the coronary insufficiency as well as surgical myocardium revascularization.